An electrochemical sensor based on iron(ii, iii)@graphene oxide@molecularly imprinted polymer nanoparticles for interleukin-8 detection in saliva1. Issue 18 (21st September 2015) - Tang, Pingping; Zhang, Hongping; Huo, Jichuan; Lin, Xiaoyan
<x xml:space="preserve">Abstract</x> An electrochemical sensor based on Fe3O4@GO@MIP nanoparticles has been proposed for interleukin-8 detection in saliva.